Linking oxidative stress biomarkers to disease progression and antioxidant therapy in hypertension and diabetes mellitus - Nuñez-Selles, Alberto J.; Nuñez-Musa, Rodolfo A.; Guillen-Marmolejos, Rafael A. (Frontiers in Molecular Biosciences, 2025)
Oxidative stress (OS) is increasingly recognized as a key factor linking hypertension (HTN) and diabetes mellitus (DM). This review summarizes recent evidence regarding the dual role of OS as both an instigator and an amplifier of cardiometabolic dysfunction. In HTN, reactive oxygen species (ROS) produced by NADPH oxidases (NOXs) and mitochondrial dysfunction contribute to endothelial impairment and vascular remodeling. In DM, hyperglycemia-induced ROS production worsens beta-cell failure and insulin resistance through pathways such as the AGE-RAGE signaling, protein kinase C (PKC) activation, and the polyol pathway. Clinically validated biomarkers of OS, such as F2-isoprostanes (which indicate lipid peroxidation), 8-OHdG (which indicates DNA damage), and the activities of redox enzymes like superoxide dismutase (SOD) and glutathione peroxidase (GPx), show strong correlations with disease progression and end-organ complications. Despite promising preclinical results, the application of antioxidant therapies in clinical settings has faced challenges due to inconsistent outcomes, highlighting the need for targeted approaches. Emerging strategies include: 1. Mitochondria-targeted antioxidants to enhance vascular function in resistant HTN; 2. Nrf2 activators to restore redox balance in early diabetes; and 3. Specific inhibitors of NOX isoforms. We emphasize three transformative areas of research: (i) the interaction between the microbiome and ROS, where modifying gut microbiota can reduce systemic OS; (ii) the use of nanotechnology to deliver antioxidants directly to pancreatic islets or atherosclerotic plaques; and (iii) phenotype-specific diagnosis and therapy guided by redox biomarkers and genetic profiling (for example, KEAP1/NRF2 polymorphisms). Integrating these advances with lifestyle modifications, such as following a Mediterranean diet and exercising regularly, may provide additional benefits. This review outlines a mechanistic framework for targeting OS in the comorbidity of HTN and DM while identifying critical knowledge gaps, particularly regarding the timing of antioxidant signaling and the development of personalized redox medicine, which may serve as a reference for researchers and clinicians working in this area.